HUBUNGAN FLEKSIBELITAS BAHU, PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN TERHADAP KETERAMPILAN SERVIS PENDEK BACKHAND BULUTANGKIS PADA ATLET PB. BANK RIAU, PEKANBARU - Sri Lasmita; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study was to get the relationship of shoulder, wrist flexibility and hand-eye coordination with the badminton skill of short service backhand at the athlete PB Bank Riau Pekanbaru. This study uses quantitative analysis descriptive correlational approach. The population in this study were as many as 6 samples. While the sample technique used is total sampling (saturated sample), where all the population as the sample. After that, the data is processed with statistics, normality test with liliefors test and correlation at significant level α (0.05). The analysis in the calculation of the correlation between X1, X2 with. Where Rtabel at significant level α (0,05) = 0,811, Then obtained for Rcount (0,842) > (0,811), which means the hypothesis is accepted and the correlation between the strength of the shoulder, wrist flexibility and hand-eye coordination with the badminton skill of short service backhand at the athlete PB Bank Riau Pekanbaru. Then the multiple correlation coefficient between the shoulder, wrist flexibility and hand-eye coordination with the short service backhand hit is significant.Keywords : Shoulder and wrist flexibility, hand-eye coordination, and short servis backhand